Identification of ferroptosis-related genes in the progress of NASH - He, Linwei; Wang, Jianming; Tao, Baihua; Zhu, Ruolan; Li, Changbing; Ning, Bo (Frontiers in Endocrinology, 2023)
Abstract Background: Non-alcoholic steatohepatitis (NASH) is becoming more widespread, and some similarities exist between its etiology and ferroptosis. However, there are limited investigations on which ferroptosis-related genes (FRGs) are regulated in NASH and how to regulate them. We screened and validated the pivotal genes linked to ferroptosis in NASH to comprehend the function of ferroptosis in the development of NASH. Methods: Two mRNA expression data were obtained from the Gene Expression Omnibus (GEO) as the training set and validation set respectively. FRGs were downloaded from FerrDb. The overlapped genes between FRGs and all genes of the training set were then analyzed by Gene Set Enrichment Analysis (GSEA). The candidate genes were obtained from the intersection between differentially expressed genes (DEGs) and FRGs, and further analyzed using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). The hub genes were identified by the protein-protein interaction (PPI) network and Cytoscape. Ultimately, these genes which are related to the progression of NASH were identified and further confirmed by the validation set and mice model. Results: A total of 327 FRGs in NASH were acquired and subjected to GSEA. And 42 candidate genes were attained by overlapping the 585 FRGs with 2823 DEGs, and enrichment analysis revealed that these genes were primarily engaged in the fatty acid metabolic, inflammatory response, and oxidative stress. A total of 10 hub genes ( IL6, SIRT1, CDKN1A, PTGS2, SCD, NQO1, CDC25A, IL1B, SLC7A11, FABP4) were then screened by PPI network. The association between the expression of 10 hub genes and the fibrosis stage was subsequently evaluated. CDKN1A and NQO1 were up-regulated along with the development of fibrosis while SIRT1 was negatively correlated with the stage of fibrosis in NASH. Finally, The relationship between three genes (NQO1, CDKN1A, SIRT1) and the progress of NASH was further confirmed in the validation set and mouse models. Conclusion: In this study, the expression of NQO1, CDKN1A, and SIRT1 was associated with progression of NASH, which may be attributed to ferroptosis, which highlight that these genes might be molecular prognostic markers and drug targets in NASH.